2021
DOI: 10.1021/acsapm.1c00321
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating Vapor Traces with Binary Brushes of Immiscible Polymers

Abstract: Vapors in the air around us can provide useful information about our environment, but we need sensitive vapor sensors to access this information, especially because those vapors are often present at very low concentrations. We report molecular dynamics simulations of a concept that can significantly increase the sensitivity of vapor sensors at low concentrations. By coating the sensor surfaces with end-anchored immiscible polymers, surface-bound polymer blends are formed that can concentrate vapors, reaching s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Microphase separation was found to become stronger with increasing grafting density, whereas the typical width of the ripple microphase decreased . Finally, recent simulation studies in our group have shown that microphase-separated brushes display enhanced vapor absorption capacity and overall solvent affinity, as the polymer–polymer interfaces form a high-energy interface that readily adsorbs solvent vapors. , …”
Section: Fundamentalsmentioning
confidence: 79%
See 1 more Smart Citation
“…Microphase separation was found to become stronger with increasing grafting density, whereas the typical width of the ripple microphase decreased . Finally, recent simulation studies in our group have shown that microphase-separated brushes display enhanced vapor absorption capacity and overall solvent affinity, as the polymer–polymer interfaces form a high-energy interface that readily adsorbs solvent vapors. , …”
Section: Fundamentalsmentioning
confidence: 79%
“…117 Finally, recent simulation studies in our group have shown that microphase-separated brushes display enhanced vapor absorption capacity and overall solvent affinity, as the polymer−polymer interfaces form a high-energy interface that readily adsorbs solvent vapors. 111,118 2.5.1. Outlook on Mixed Brushes.…”
Section: Introductionmentioning
confidence: 99%
“…We confirm that equilibrium is reached by observing that polymer density profiles no longer change with time. After the equilibrium is reached, we start the production run (3*10 6 time steps) where the vapor is introduced to the system via GCMC method (constant µV T ) 26,28 . During this production run, particle density profiles and snapshots are generated.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The mixed binary brush system consists of equal fractions of homopolymers consisting of each monomer species, and is investigated for comparison to previous work. 28,29 We consider the solvent fraction as a function of the relative solvent pressure, which we define as the solvent pressure normalized by the saturation pressure of the vapor. In Fig.…”
Section: Isothermsmentioning
confidence: 99%
“…chameleons. 20 Next to these bioinspired approaches, brushes can also be applied in smart adhesives, 21,22 energy devices, 23,24 bactericidal [25][26][27] and blood compatible 28,29 coatings, membranes, 30,31 nano-theranostics, 32 sensing [33][34][35] and many more applications. [36][37][38][39] End-anchored polymers can adopt different conformations.…”
Section: Introductionmentioning
confidence: 99%